Brain Informatics International Conference, BI 2011, Lanzhou, China, September 7-9, 2011. Proceedings - Hu, Bin.; Liu, Jiming; Chen, Lin.; Zhong, Ning.; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the International Conference on Brain Informatics, BI 2011, held in Lanzhou, China, in September 2011. The 27 revised full papers and 6 keynote talks were carefully reviewed and selected for inclusion in the book. They are grouped in topcial sections on thinking and perception-centric investigations of human information processing systems; information technologies for the management, analysis and use of brain data; cognition-inspired applications. Furthermore, there is a section with 8 papers from the workshop on meta-synthesis and complex systems.
Electronic reproduction.
Keywords: Computer science; Computer software; Database management; Information systems; Artificial intelligence; Computer vision; Neural networks (Computer science) -- Congresses; Brain -- Physiology -- Congresses; Computer science -- Congresses; Human information processing -- Congresses; Brain -- physiology -- Congresses; Automatic Data Processing -- Congresses; Mental Processes -- Congresses